Implementación de un material compuesto utilizando polvo de neumático, para la fabricación de piso flexible para el uso en talleres automotrices. - Llumitasig Calvopiña, Mario Javier (2021)
The titulation work got a composite material with the shape and dimensions of a tile using tire dust from tires out of use which is discarded and ends up in sinks, rivers and finally the sea, through crushing processes the Tire powder and taking advantage of its mechanical characteristics can be used as a matrix to form a composite material together with a binder such as liquid polyurethane in a suggested concentration of 20% and under pressure and temperature conditions provided by a pressing machine, we have the composite material by harnessing approximately 99% of the raw material, specimens were made according to the specifications of the ASTM D638 and D2240 standards to establish their mechanical properties, traction and hardness respectively, having values of 68 in hardness on the Shore A scale to be used as a coating on a floor of an automotive workshop. guaranteeing a flexible floor and its durability.